The Interplay Between Religion, Traditional Beliefs, and Socio-Economic Development: Insights from Four Emerging Economies - Harakan, Ahmad; Kinyondo, Abel; Kepko, Yao Moise; Kuzenbayev, Nygmetzhan; Pelizzo, Riccardo (IAIN Manado, 2024)
This article explores the relationship between traditional beliefs, socio-economic development, and religion in four emerging economies: Benin, Indonesia, Tanzania, and Togo. The study addresses gaps in existing literature, which has not conclusively determined whether and to what extent socio-economic development reduces the prevalence of traditional beliefs. Additionally, the interplay between religion and traditional beliefs remains debated, with some studies suggesting coexistence while others highlight inherent conflicts. The findings reveal that the impact of socio-economic development on traditional beliefs varies significantly across different types of beliefs. From an Islamic law perspective, practices such as witchcraft and superstition are condemned as shirk (polytheism) for diverting reliance away from Allah. Islamic jurisprudence (fiqh) and principles like maqasid al-shariah (objectives of Sharia) provide frameworks to counter these practices by promoting rationality, education, and monotheism. In Indonesia, for instance, Islamic principles have allowed traditional healing practices to coexist with modernity within an ethical framework aligned with Sharia. Conversely, in regions with smaller Muslim populations, such as Benin and Togo, traditional beliefs remain widespread and are often intertwined with animism and other non-Islamic faiths. The study also finds that religious demography significantly influences the persistence of some traditional beliefs but not others. Finally, it highlights a strong correlation between the popularity of traditional beliefs and the prominence of traditional religions within societies.